The Impact of Industrialization on The Regional Economic Development and Community Welfare - Sutikno Sutikno; Muhammad Sri Wahyudi Suliswanto (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2017)
This study was aimed to determine the impact of industrialization on the regional economic development. Gresik regency was chosen as the research setting for it is one of largest industrial areas in East Java. The analysis instruments used were: First, the regression analysis, to determine the impact of industrialization on economic growth, unemployment, and poverty. Second, Confirmatory Factor Analysis (CFA), it was used to investigate the impact of industrialization on the community welfare. Third, Monte Carlo simulation that used to formulate a recommendation. The result showed that the industrialization in Gresik still has not been able to give extensive significant impact for the community in Gresik regency and its existence can only be enjoyed by nearby residents. Based on the simulation results, showed that the strong commitment between Gresik local government and the industry in order to address the problem of unemployment is very necessary due to its’ greatest impact.DOI: 10.15408/sjie.v6i2.5334